Antimicrobial Efficacy of Myrmecodia pendens Extract and Fraction Combination against Enterococcus faecalis ATCC 29212 - Kuswandani, Faisal; Satari, Mieke H; Maskoen, Ani M (UI Scholars Hub, 2019)
Enterococcus faecalis can withstand harsh environmental conditions in the root canal and cause a secondary infection. Myrmecodia pendens is an herbal medicine rich in polyphenol compounds that have antibacterial, antioxidant, and anticancer properties. Objectives: To analyze the effects of M. pendens fraction combination on the sensitivity of E. faecalis. Methods: The minimum inhibitory concentration (MIC) was determined using a serial microdilution method, and the minimum bactericidal concentration (MBC) was determined by adding the test sample to sterile Mueler Hinton agar medium. Results: The MIC of combination 1 (hexane-ethyl acetate, HE) was 0.049 mg/mL, whereas those of combinations 2 (hexane-water, HA) and 3 (ethyl acetate-water, EA) were 0.098 and 0.390 mg/ mL, respectively. The MIC of NaOCl was 0.390 mg/mL, and that of methanol extract was 0.390 mg/mL. The MBC of combination 1 (HE) was 12.50 mg/mL, whereas that of combinations 2 (HA) and 3 (EA) was 50 mg/mL. The MBC of NaOCl was 25 mg/mL and that of methanol extract was 50 mg/mL against E. faecalis. This study showed that fraction combinations increase the antibacterial effect of M. pendens against E. faecalis ATCC 29212. Conclusion: The HE fraction combination showed the best effect against E. faecalis and can be developed as an alternative endodontic irrigant